PINDAR AND THE BEES: A WASPISH REPLY - White, Heather (Myrtia, 2004)
This epigram has recently been discussed by Staffan Fogelmark: cf. Eranos 100, 2002, 128-136, "To Bee Or Not To Bee? Antipater A.P.7, 34 A Mistaken Interpretation". Fogelmark refers the reader to the discussion of this epigram in my New Essays In Hellenistic Poetry (Amsterdam 1985), page 69ff. According to F. my treatment of this epigram "is of little help as it not only repeats but even adds to the misunderstandings of previous scholars". The reader will note that F. is of the opinion that the theories of other scholars are worthless, and that he alone is capable of understanding the poet’s words.